Investigation on carbon nanotube electronics structure - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz; Motakabber, S. M. A. (penseejournal.com, 2013)
In this paper, Graphenes’ electronic structure of carbon nanotubes is analyzed. The analysis is done to calculate energy dispersion relation, effective mass and intrinsic carrier concentration of graphene to establish different carbon nanotubes. Diameters with different chiral vector (n, m) of carbon nanotubes vary the electronics properties of graphene. Different chiral vector of a graphene allows designing carbon nanotube (CNT) for different types of appliance, which can be achieved from the analyzed carrier concentration calculation. This investigation will helpful for further designing of CNT-based nano device.